Diagnostic value of full-mouth radiography in horses - Bishop, Ian Tyler (Frontiers in Veterinary Science, 2022)
Oral exams and full-mouth dental radiographs were performed on 248 horses presented for routine oral health care. The findings were assessed to determine how often disease was diagnosed by radiographs without related findings on oral exam. In 21.0% of cases, there were important radiographic findings that would not have been predicted based upon the oral exam. 45.6% of cases had oral exam findings that would have prompted dental radiographs, according to the criteria of the study, and of those 21.2% had radiographic signs of disease that would have been missed if only targeted radiographs had been taken, rather than a full-mouth survey.